The Ecological Veto in Islamic Law: Reconstructing Natural Resource Governance from Prophetic Precedents - Muhammad Zainuddin Zidan; Ali Mas’ud (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2026)
Extractive industrial practices increasingly exacerbate global socio-ecological degradation, revealing the structural limitations of conventional market-driven governance and economic cost-benefit models in internalizing environmental damage. While contemporary environmental literature offers technocratic frameworks, existing Islamic legal scholarship remains divided between abstract eco-theological norms that lack operational legal enforceability and secular administrative regimes that bypass religious jurisprudence. To address this gap, this study examines the historical-normative precedents of early Islamic natural resource statecraft as its primary object of analysis. Employing a qualitative historical-normative design, this research utilizes uṣūlī hermeneutical methods, specifically takhrīj al-manāṭ (extraction of legal ratio legis), and the analytical framework of maqāṣid al-sharī‘ah to evaluate canonical Hadith records regarding the revocation of Abyad bin Hammal’s salt mining concession and the institutionalization of the ḥimā Al-Naqī conservation zone. The findings demonstrate that early Islamic jurisprudence establishes an operational "ecological veto" mechanism: natural resource concessions operate not as perpetual private property rights, but as conditional public trusts (amānah) subject to mandatory revocation if they compromise ecological equilibrium or public access. Theoretically, this study reorients ḥifẓ al-māl from monetary asset accumulation to the preservation of natural capital. Practically, it proposes actionable regulatory reforms for modern mining policies, including non-automatic permit renewals, strict liability through upfront ecological bonds (al-kharāj bi al-ḍamān), and binding mining moratoriums in critical ecosystems. Ultimately, this research confirms that Islamic legal precedents offer a binding constitutional framework capable of constraining market externalities